Association between prolonged neutropenia and reduced relapse risk in pediatric AML: A report from the children's oncology group. Issue 9 (4th July 2016) - Sung, Lillian; Aplenc, Richard; Alonzo, Todd A.; Gerbing, Robert B.; Wang, Yi‐Cheng; Meshinchi, Soheil; Gamis, Alan S.
Abstract : Objective was to describe the relationship between the number of sterile site infections and duration of neutropenia during the first four cycles of chemotherapy and the risk of recurrence and overall survival in children with newly diagnosed acute myeloid leukemia (AML). AAML0531 was a Children's Oncology Group randomized phase 3 clinical trial that included 1022 children with de novo AML. For this analysis, we focused on non‐Down syndrome favorable and standard risk patients who completed at least 4 cycles of chemotherapy without recurrence or withdrawal during protocol therapy. Those receiving hematopoietic stem cell transplantation in first remission were excluded. Five hundred and sixty‐nine patients were included; 274 (48.2%) were favorable risk. The median cumulative time with neutropenia between Induction II to completion of Intensification II was 96 (range 54–204) days. Number of sterile site infections did not influence the risk of relapse or overall survival. However, longer duration of neutropenia was associated with a lower risk of relapse (hazard ratio 0.81 per 20 days neutropenia, p = 0.007). Longer duration of neutropenia was associated with a reduced risk of relapse for children with favorable and standard risk AML. Toxicity may be influenced by pharmacogenomics suggesting that individualized chemotherapy dosing may be an effective strategy. Abstract : What's New? Treatment responses vary considerably among children with acute myeloid leukemia (AML), leaving some children at risk of severe toxicity and others at risk of suboptimal systemic exposure. The present study shows that for children and young adults with favorable and standard risk AML, variations in treatment response significantly impact risk of disease relapse. In particular, duration of neutropenia during the first four cycles of chemotherapy was found to be inversely associated with relapse risk. The degree of neutropenia experienced may be influenced by genetic factors, suggesting that individualized chemotherapy dosing may be an effective strategy in pediatric AML.